"Changes in cartilage of rats after treatment with Quinolone and in Magnesium-deficient diet " - Shakibaei M; Stahlmann R (Acta Medica Iranica, 2002)
Ultrastructural changes in immature articular carilage were studied after treatment of 5-weeks-old rats with ofloxacin, a fluoroquinolone, and in magnesium deficiency.We concluded that quinolone-induced arthropathy is probably due to chelation of functionally available magnesium in joint cartilage as magnesium deficiency in joint cartilage could impair chondrocyte-matrix- interaction which is mediated by cation-dependent integrin-receptors of the β1-subfamily. With immuno-histochemical methods using monoclonal and polyclonal antibodies we showed that B1 integrins were expressed in rat joint cartilage. Joint cartilage lesions were detected in ofloxacin-treated and magnesium-deficient rats. Lesions were more pronounced in the quinolone-treated group. Expression of several integrins was reduced in the vicinity of lesions after oral treatment with 2×600 mg ofloxacin/kg body wt for one day. Gross-structural lesions (e.g. cleft formation, unmasked collagen fibres) in magnesium deficient rats were very similar but changes in intergrin expression were less pronounced. Alterations observed on the ultrastructural level showed striking similarities in magnesium-deficient rats and in rats treated with single doses of 600 mg ofloxacin per kg body wt.Typical observation were: bundle shaped, electron-dense aggregates on the surface and in the cytoplasm of chondrocytes, detachement of the cell membrance from the matrix and necrotic chondrocytes, reduced synthesis and/or reduced of extracellular matrix and swelling of cell organelles such as mitochondria.The results of this study confirm our previously reported finding that quinolone-induced arthropathy probably is caued by a reduction of functionally available magnesium (ionized Mg2+) in cartilage. Furthermore, they provide a basis for aimed studies with human cartilage samples from quinolone-treated patients which might be available postmortal or after hip replacement surgery